Social Comparison dan Kecenderungan Body Dissatisfaction Pada Wanita Dewasa Awal Pengguna Instagram (SUKMA : Jurnal Penelitian Psikologi, 2020)
Body dissatisfaction is the feeling, thought and negative judgment of dissatisfaction gained from individual evaluation of his body that is influenced by an individual's perspective on his body and social environment which also provides the standards of beauty in the community. One of the factors affecting body dissatisfaction is the social comparison. The research aims to determine the relationship between social comparison and the tendency of body dissatisfaction in early adult women of Instagram users. Selection of participants using Purposive Sampling technique with participants as many as 100 subjects with criteria; 1) Women aged 18-25 years, 2) active users of Instagram, 3) domiciled in Surabaya. The collection of data was done by using the scale-up of Rosen & Reiter body dissatisfaction and the development of Festinger scale social comparison. Data analysis methods using Pearson Product Moment. Data analysis results show a correlation coefficient of (Rxy) = 0.729 with significance p = 0.000 (p<0.01). The results showed a significant positive relationship between  social comparison and body dissatisfaction. Keyword: Body Dissatisfaction; Early Adult; Social Comparison